2022
DOI: 10.3389/fmed.2021.762878
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Cell Signaling in Pulmonary Emphysema

Abstract: Pulmonary emphysema is characterized by the destruction of alveolar septa and irreversible airflow limitation. Cigarette smoking is the primary cause of this disease development. It induces oxidative stress and disturbs lung physiology and tissue homeostasis. Alveolar type II (ATII) cells have stem cell potential and can repair the denuded epithelium after injury; however, their dysfunction is evident in emphysema. There is no effective treatment available for this disease. Challenges in this field involve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 123 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…Increasing evidence shows multiple dysregulated signaling pathways in ATII cells in emphysema [25,28,46], contributing to apoptosis/proliferation imbalance and alveolar destruction. Besides, less responsive mesenchymal cells [8] and dysfunctional endothelium [63] were observed in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence shows multiple dysregulated signaling pathways in ATII cells in emphysema [25,28,46], contributing to apoptosis/proliferation imbalance and alveolar destruction. Besides, less responsive mesenchymal cells [8] and dysfunctional endothelium [63] were observed in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, characteristics of cellular senescence were observed in emphysema patients [46]. Treatments targeting cellular senescence have beneficial effects on animal models of emphysema.…”
Section: Therapeutic Targets In Emphysema 61 Therapeutics and Emergin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, alpha-1 antitrypsin deficiency, which is a rare genetic risk factor, may induce early disease occurrence [215] . The pathogenesis of pulmonary emphysema involves the dysregulation of various signalling pathways, including oxidative stress, defective antioxidant defence systems, inflammatory responses, and cell dysfunction [216] . A study showed that treatment with 100 µM LA could scavenge hypochlorous acid in vitro [217] , impairing hypochlorous acid-mediated inactivation of alpha-1-antiproteinase and elastase and reducing the damage associated with lung emphysema .…”
Section: Lipoic Acid and Respiratory Diseasesmentioning
confidence: 99%